Adjuvant cardioprotection in cardiac surgery: update - Wagner, Robert; Piler, Pavel; Gabbasov, Zufar; Maruyama, Junko; Maruyama, Kazuo; Nicovsky, Jiri; Kruzliak, Peter (BioMed research international, 2014)
Cardiac surgery patients are now more risky in terms of age, comorbidities, and the need for complex procedures. It brings about reperfusion injury, which leads to dysfunction and/or loss of part of the myocardium. These groups of patients have a higher incidence of postoperative complications and mortality. One way of augmenting intraoperative myocardial protection is the phenomenon of myocardial conditioning, elicited with brief nonlethal episodes of ischaemia-reperfusion. In addition, drugs are being tested that mimic ischaemic conditioning. Such cardioprotective techniques are mainly focused on reperfusion injury, a complex response of the organism to the restoration of coronary blood flow in ischaemic tissue, which can lead to cell death. Extensive research over the last three decades has revealed the basic mechanisms of reperfusion injury and myocardial conditioning, suggesting its therapeutic potential. But despite the enormous efforts that have been expended in preclinical studies, almost all cardioprotective therapies have failed in the third phase of clinical trials. One reason is that evolutionary young cellular mechanisms of protection against oxygen handling are not very robust. Ischaemic conditioning, which is among these, is also limited by this. At present, the prevailing belief is that such options of treatment exist, but their full employment will not occur until subquestions and methodological issues with the transfer into clinical practice have been resolved.
Keywords: Cardiotonic Agents; kardiochirurgické výkony; Cardiac Surgical Procedures; kardiotonika; Clinical Trials as Topic; adjuvancia farmaceutická; Humans; výsledek terapie; lidé; ischemický postconditioning; Treatment Outcome; Adjuvants, Pharmaceutic; Ischemic Postconditioning; klinické zkoušky jako téma